Transcending school: the continental impact of the Argentine educator Olga Cossettini, based on the experience of El niño y expresión, in the 1940s. - Fernandez, Sandra Rita (Paedagogica Historica, 2019)
In the early 1940s Olga Cossettini, an Argentine teacher, received missives from several representatives of the cultural and educational world of the Americas. The event that allowed Cossettini's international relevance was the school artwork exhibition that took place in November 1939 in the Castagnino museum in the city of Rosario (Argentina). This experience surpassed the actual event when in 1940 a book of the same name as the exhibition was published. Its distribution led to Cossettini being invited personally by Henry Allen Moe to apply for the Guggenheim Fellowship. What is more, the distribution of the book also made her name and work known in Pan-American organisations of different types. The aim of this article is to put forward the personal and institutional networks and contacts that Cossettini developed throughout a given period in her career. A clear example of this is Ego, which allows us to observe the shaping process of pan-American intellectual connections. These connections included ideas that although founded in educational experiences, transcended their boundaries.